68. Painful laser evoked potential inhibition during high-frequency non-noxious somatosensory stimulation. Issue 12 (December 2017) - Valeriani, M.; Pazzaglia, C.; Rizzo, V.; Quartarone, A.; Vollono, C.
Abstract : The neurophysiological mechanism subserving the analgesia induced by rubbing the painful part of the body or during TENS is still unknown. Our aim was to investigate the site of this inhibition. We studied 10 healthy volunteers. LEPs were recorded after stimulation of the radial and ulnar territories of both the right and left hand dorsum in 2 conditions: (1) no conditioning stimulation (baseline condition), and (2) high-frequency (5 Hz) non-painful electrical stimulation of the right radial nerve (gating condition). As compared to the baseline, in the gating condition the N2/P2 amplitude was reduced in amplitude after stimulation of the radial territory of both hands ( p  < 0.001 and p  < 0.001 for right and left hand, respectively) and of the right ulnar region ( p  = 0.008), while no inhibition was found to left ulnar region stimulation ( p  = 0.06). High-frequency non-painful stimulation of the right radial nerve inhibits the nociceptive input coming from both the ipsilateral and contralateral homotopic regions, and from a close ipsilateral heterotopic territory. On the contrary, it does not have any effect on the nociceptive input due to stimulation of a contralateral heterotopic area. Our results suggest that spinal segmental inhibitory mechanisms are mainly involved.